Asymmetric Stepwise Reductive Amination of Sulfonamides, Sulfamates, and a Phosphinamide by Nickel Catalysis. Issue 1 (5th December 2018) - Zhao, Xiaohu; Xu, Haiyan; Huang, Xiaolei; Zhou, Jianrong Steve
Abstract: Asymmetric reductive amination of poorly nucleophilic sulfonamides was realized in the presence of nickel catalysts and titanium alkoxide. A wide range of ketones, including enolizable ketones and some biaryl ones, were converted into sulfonamides in excellent enantiomeric excess. The cyclization of sulfamates and intermolecular reductive amination of a diarylphosphinamide were also successful. Formic acid was used as a safe and economic surrogate of high‐pressure hydrogen gas. Abstract : Amines with attenuated nucleophilicity, including sulfonamides, sulfamates, and phosphinmaides, undergo enantioselective reductive amination in the presence of nickel catalysts, titanium alkoxide, and formic acid as the hydrogen source. The procedure is applicable to a diverse range of ketones, including enolizable aliphatic ketones and some biaryl ketones.